Nowe regulacje dotyczące wykonywania kary pozbawienia wolności wobec osadzonych stwarzających poważne zagrożenie społeczne albo poważne zagrożenie dla bezpieczeństwa zakładu karnego - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The study is devoted to the principles of implementing imprisonment for prisoners who pose a serious social threat or a serious threat to the security of the facility, not regulated in the Executive Penal Code. It was indicated at the outset that the provisions of the Act regulate the title issue quite synthetically. The Act on the Prison Service specifies that the Director General of the Prison Service, as part of their duties, may issue orders, instructions or guidelines. Both of these legal acts specify in detail the provisions of the Executive Penal Code, which are devoted to, e.g., the rules for implementing imprisonment for this particular category of convicts.
Keywords: dangerous convict; prison sentence; order; maximum security wings; prison